IMPRESSIONISTIC-SYMBJLISTIC COORDINATES OF THE WORK BY ROMAN KUPCHINSKY “SELO” - Melnyk, M. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article is devoted to the manuscripted work of R. Kupchinsky. It emphasisez the fact that the poetry containing in his work was written in the period of the author’s activity in the “Mytusa” and his sympathy to symbolism and kyivskyi symbolists experience from “Muzahet”. The work considers to be an peculiar lyrical diary, where he reveals his actual thoughts and feelings about the world.